Productions agricoles, stockage et finage en Montagne Noire médiévale Le grenier castral de Durfort (Tarn) - Ruas, Marie-Pierre (Documents d'archéologie française, 2002)
Carpalogical research combined with careful field methodology provides an exemplary illustration of the potential for an approach only recently applied to historical periods In France. The stocks from the Durfort granary, destroyed by tire in the 14th century, have provided an opportunity to study almost 400,000 seeds from the same occupation layer. The corpus of 157 taxa, composed of 26 cultivated and 131 wild plants, has provided a large number of research opportunities. Carpological analysis, earned out in conjunction with archival research, has produced remarkable information in areas ranging from spatial distribution of grain species in the storage structure to hypotheses on farming practices on medieval community lands in a medium mountain context. The results demonstrate the importance of this contribution to our knowledge at agrarian history and material culture.